Distinct genetic lineages of Bactrocera caudata (Insecta: Tephritidae) revealed by COI and 16S DNA sequences - Lim, Phaik Eem; Tan, Ji; Suana, I. Wayan; Eamsobhana, Praphathip; Yong, Hoi Sen (Public Library of Science, 2012)
The fruit fly Bactrocera caudata is a pest species of economic importance in Asia. Its larvae feed on the flowers of Cucurbitaceae such as Cucurbita moschata. To-date it is distinguished from related species based on morphological characters. Specimens of B. caudata from Peninsular Malaysia and Indonesia (Bali and Lombok) were analysed using the partial DNA sequences of cytochrome c oxidase subunit I (COI) and 16S rRNA genes. Both gene sequences revealed that B. caudata from Peninsular Malaysia was distinctly different from B. caudata of Bali and Lombok, without common haplotype between them. Phylogenetic analysis revealed two distinct clades, indicating distinct genetic lineage. The uncorrected 'p' distance for COI sequences between B. caudata of Malaysia-Thailand-China and B. caudata of Bali-Lombok was 5.65%, for 16S sequences from 2.76 to 2.99%, and for combined COI and 16S sequences 4.45 to 4.46%. The 'p' values are distinctly different from intraspecific 'p' distance (0-0.23%). Both the B. caudata lineages are distinctly separated from related species in the subgenus Zeugodacus - B. ascita, B. scutellata, B. ishigakiensis, B. diaphora, B. tau, B. cucurbitae, and B. depressa. Molecular phylogenetic analysis indicates that the B. caudata lineages are closely related to B. ascita sp. B, and form a clade with B. scutellata, B. ishigakiensis, B. diaphora and B. ascita sp. A. This study provides additional baseline for the phylogenetic relationships of Bactrocera fruit flies of the subgenus Zeugodacus. Both the COI and 16S genes could be useful markers for the molecular differentiation and phylogenetic analysis of tephritid fruit flies.